Analisis Hukum Islam terhadap Jual Beli Online - Ghifari, Abu Dzar Al; Nasution, Yenni Samri Juliati (Ikatan Da'i Indonesia, 2023)
One of the mu'amalah phenomena in the economic field is buying and selling transactions that use electronic media, technological developments have spurred changes in individual habits including one of them in terms of buying and selling transactions. If in the past what was meant by buying and selling transactions had to be carried out face to face where there was a direct transfer of goods from the seller to the buyer, that is the buyer had to meet the seller in the real market. Judging from the type of research, there is also the type of research used in this research, namely bibliography research or library research, which is research that is carried out by collecting information or making objective records that mean the object of research or collecting information that has the character of a bibliography, or analysis carried out to unravel a problem which is basically based on critical and in-depth analysis of relevant literature materials. This research results that in online sales it fulfills the pillars of the contract in accordance with the rules of fiqh. As is well known, there are four pillars of contract, namely: (a); there are contracting parties; (b) consent and acceptance; (c) the object of the contract; (d) the main purpose of the contract is carried out.